Modulação autonômica cardíaca e a influência da noradrenalina frente à mobilização passiva em pacientes com choque séptico - Melger, Maria Julia Checo (Universidade Federal de São Carlos, 2020)
Introduction: Sepsis is currently one of the main causes of hospital death and when associated with the use of vasopressor medication and lactate> 2mol mmol / L is defined as septic shock. This patient has impairment in the sympathetic and parasympathetic autonomic nervous system (ANS). In addition, for these hospitalized and bedridden patients, passive mobilization is a widely used strategy, but there is still a lack of evidence on the association between vasoactive medication in the cardiac autonomic response. Objective: To investigate the presence of an association between vasoactive drugs and the response of cardiac autonomic modulation to passive mobilization in patients with septic shock. Methods: Prospective interventional study. The sample consisted of 16 individuals diagnosed with septic shock. The heart rate variability (HRV) indices were analyzed: DFA, PNS, BF / AF and RMSSD, in the pre, during and post mobilization moments, as well as the HRV variations (deltas: ∆mob-pre, ∆post-mob and (Post-pre). To verify the association between the use of noradrenaline and HRV, Spearman's correlation coefficient was used, with a significance level of 5% (p <0.05). Results: Correlations were found between noradrenaline and the HRV variation, as shown: negative correlations between 1. noradrenaline and the DFA1 index (r = -0.64; p = 0.009) and 2. Noradrenaline and BF / AF ratio (r = -0.49; p = 0.05) for post-premob delta and mob-pre delta, respectively. In addition to 3. positive correlations between noradrenaline and the PNS index (r = 0.54; p = 0.032) for mob-pre delta. Conclusion: noradrenaline is associated with the response of cardiac autonomic modulation to passive mobilization in patients with septic shock.
Cardiac autonomic modulation and influence of noradrenaline to passive mobilization in patients with septic shock
Keywords: Mobilização precoce; Early mobilization; Intensive care; Cuidado intensivo; Fisioterapia; Physiotherapy; Sepsis; Sepse; Vasoactive drug; Droga vasoativa; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL